KINERJA PEGAWAI DI BADAN PENANAMAN MODAL DAERAH (BPMD) KABUPATEN KUTAI TIMUR - ., Murtiningsih (EKONOMIA, 2013)
The purpose of this study was to determine the influence of leadership style, Education and Training, and Discipline motivasi Work on Employee Performance in the Regional Investment Board (BPMD) East Kutai regency.Analysis model is used to prove the hypothesis is a model of multiple linear regression analysis with the number of respondents 58 permanent employees and temporary employees (PTT) in the Regional Investment Board (BPMD) East Kutai regency.Statistical analysis showed regression coefficients independent variables, namely Leadership Style (X1) = 0.100, Education and Training (X2) = 0.036, Work Environment (X3) = -0.204, Work Motivation (X4) = 0.148 and Work Discipline (X5 ) = 0.744 and -1.077 constant at the value obtained from the linear regression equation gerganda are:Y = 0.358 +0.347 +0.1 X1 + X2 (-0.204 +0.744 X3 +0.148 X4 X5From the results obtained by analysis of the correlation coefficient R value of 0.707, which means jointly Leadership Style variable (X1), Education and Training (X2), Work Environment (X3), Work Motivation (X4) and Work Discipline (X5) has a relationship Strong on employee performance in the Regional Investment Board (BPMD) East Kutai regency.It is shown from the results of the determinant coefficient (R2) of 0.562, which means that the performance of employees in the Regional Investment Board (BPMD) East Kutai Regency influenced by leadership style variable (X1), Education and Training (X2), Work Environment (X3), Work Motivation (X4) and Work Discipline (X5).Results of this study indicate that all independent variables simultaneously have a significant influence on the performance of employees in the Regional Investment Board (BPMD) East Kutai Regency, it is shown from the results of the F test was 6.028 greater than F table 2.38 and Sig. Of 0.00 is smaller than alpha of 0.05.The results also indicate the dominant variables that affect the performance of the Work Discipline t test was the highest count that is equal to 4,626 and the highest beta value of 0.744 significant at 0.000 <0.05.F test and t-test proved that the first hypothesis and the second hypothesis is accepted.